Font Designing Using Generalized Ball Basis - ABDUL KARIM, SAMSUL ARIFFIN (2010)
Cubic Ball polynomials were proposed by Ball and subsequently used by British Aircraft Cooperation at Warton. Its generalization to higher degrees were proposed independently by Said (known as Said-Ball) and Wang (known as Wang-Ball). Later, Delgado & Pena proposed new basis functions as generalised Ball basis functions of any degree which are known as DP basis. Subsequently, Dejdumrong has introduced new type of generalized Ball basis known as Dejdumrong-Ball basis. In this paper, we study the prospect of using Generalized Ball curves in designing fonts which satisfy the geometric condition G0 and G1 at their joint. We hope that this scheme could provide a greater flexibility to the font designer. Several numerical results will be presented.